Painting for performance : a beginner's guide to great painted scenery - O'Skea, Sean (Routledge, Taylor & Francis Group, 2017)
"Covering the mechanics of paint and its many implementations in set design, this book provides simple and effective step-by-step instructions for painting a variety of surfaces to look great onstage."--Back cover.